Genomic Characterization of a Novel Freshwater Cyanophage Reveals a New Lineage of Cyanopodovirus - Zhang, Dong; He, Yiliang; Gin, Karina Yew-Hoong (Frontiers in Microbiology, 2022)
Cyanobacteria are one of the dominant autotrophs in tropical freshwater communities, yet phages infecting them remain poorly characterized. Here we present the characterization of cyanophage S-SRP02, isolated from a tropical freshwater lake in Singapore, which infects Synechococcus sp. Strain SR-C1 isolated from the same lake. S-SRP02 represents a new evolutionary lineage of cyanophage. Out of 47 open reading frames (ORFs), only 20 ORFs share homology with genes encoding proteins of known function. There is lack of auxiliary metabolic genes which was commonly found as core genes in marine cyanopodoviruses. S-SRP02 also harbours unique structural genes highly divergent from other cultured phages.Phylogenetic analysis and viral proteomic tree further demonstrate the divergence of S-SRP02 from other sequenced phage isolates. Nonetheless, S-SRP02 shares synteny with phage genes of uncultured phages obtained from the Mediterranean Sea deep chlorophyll maximum fosmids, indicating the ecological importance of S-SRP02 and its related viruses. This is further supported by metagenomic mapping of environmental viral metagenomic reads onto the S-SRP02 genome.